MatStick: Changing the material sensation of objects upon impact - Songxian Liu; Jian He; Shengsheng Jiang; Ziyan Zhang; Mengfei Lv (Virtual Reality & Intelligent Hardware)
An increasing number of studies have focused on providing rich tactile feedback in virtual reality interactive scenarios. In this study, we addressed a tapping scenario in virtual reality by designing MatStick, a solution capable of offering diverse tapping sensations. MatStick utilizes a soft physical base to provide force feedback and modulates the instantaneous vibration of the base using a voice coil motor, thereby altering the perception of the base material. We conducted two psychophysical experiments and a subjective evaluation to assess the capabilities of MatStick. The results demonstrate that MatStick can deliver rich tapping sensations. Although users may find it challenging to directly correlate the tapping sensation with the actual physical material based solely on tactile feedback, in immersive scenarios combined with visual and auditory cues, MatStick significantly enhances the user's interaction experience.